Relevance Of Economic Analysis On The Problemas Of Rural Welfare - Knight, Peter T. (1974)
First, the article presents the analysis of the term “rural welfare” and the relationship between welfare (rural or any other), individual values and analytical methods. The second part deals with the limitations of economic analysis which are very common when it analyzes the rural and urban sectors. Third, it explains a brief examination of two possible alternatives to the economic research: interdisciplinary research and the development of an integral social science. Finally, it describes the relationship between some of these ideas and the design and evaluation of rural development, suggesting a research agenda.